A contrarian in search of tradition: post-war American education and the career of Diane Ravitch - Ashurst, Graham (2025)
This thesis assesses the career of Diane Ravitch (born 1938) who has influenced American school education in a range of ways — as an historian, commentator and adviser, and as a government official — since the 1960s. Based on a chronological chapter structure, the thesis argues that during her working life, Ravitch has retained certain ‘traditionalist’ ideas, based on support for public schools, the teaching profession, a liberal arts curriculum, and shared American values, but that the way in which she has upheld these ideas has evolved in response to shifts in politics, culture and intellectual life. Having been a liberal Democrat believing in the statist, pro-labour principles of the New Deal, she responded to the challenge to her views posed by the countercultural New Left by joining forces with the right-of-centre neoconservatives. She remained associated with neoconservatism for 40 years, playing an active part in its work on school standards, but refrained from adopting the pro-market ideas increasingly popular among neoconservatives and promoted vociferously by neoliberals until — in what proved to be an exceptional episode in her career — she endorsed the 1990s ‘reform agenda’ of standardised testing, teacher/school ‘accountability’ and ‘school choice’. Realising in the late 2000s that the radical neoliberalism inherent in ‘reform’ was alien to her core principles, and displaying the contrarian instincts which led her to challenge fashionable ideas of the day, she turned away from her neoconservative allies and lent her vigorous support to the centre-left activists fighting for public education and teachers’ rights. The thesis argues that, in defending her traditional ideas first against the left and more latterly against the right, Ravitch has displayed an underlying consistency and continuity in a period of major change.